Standardization of compost and casing for milky mushroom production (Zoo Botanica, 2025)
Mushroom is a fungus that includes various species of the Tricholomataceae family and belongs to the phylum Basidiomycetes. After button and oyster mushrooms, milky mushroom (Calocybe indica) has high protein value with low fat content. C. indica contains a significant number of essential amino acids, protein (28%), vitamins (49%), fiber (14%), and low-fat (4%) food. C. indica has long been valued as a nutritional supplement, rich in thiamine, riboflavin, nicotinic acid, biotin, pyridoxine, and ascorbic acid. The current study aimed to determine the most suitable substrate and casing material for the successful cultivation of milky mushrooms. Three substrates, viz., wheat straw substrate, paddy straw substrate, and sugarcane bagasse substrate, were used for the production of C. indica and these substrates were obtained from the University Research Farm, Koont. Two types of methods (steam pasteurization and chemical pasteurization) were used for the pasteurization of compost. However, heat steam pasteurization showed highly significant results in the mycelial growth after the 7th, 14th and 21st days. Four casing (peat moss casing, coconut moss casing, rice husk casing, and clay soil casing (control)) were used for this experiment. Steam-pasteurized of wheat straw with peat moss casing was found to be the most effective combination for optimal growth and yield of C. indica.
Keywords: Standardization; compost; casing